PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI DAN KINERJA KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENINGNYA - Delfi Kurnia Zebua, (Jurnal Cakrawala Ilmiah, 2023)
This study aims to examine the role of job satisfaction as a mediation between organizational culture on organizational commitment and work performance. Primary data in this study were obtained from a survey using 89 questionnaires at the BAPEDA in West Sumatra province which produced a sample of 84 respondents. The analysis revealed that organizational culture had a positive and significant effect on job satisfaction, organizational commitment, and work performance. specifically, this study also found that job satisfaction mediates the relationship between organizational culture, organizational commitment and work performance.